Autophagy-related direct membrane import from ER/cytoplasm into the vacuole or apoplast: a hidden gateway also for secondary metabolites and phytohormones? - Kulich, Ivan; Žárský, Viktor (International journal of molecular sciences, 2014)
Transportation of low molecular weight cargoes into the plant vacuole represents an essential plant cell function. Several lines of evidence indicate that autophagy-related direct endoplasmic reticulum (ER) to vacuole (and also, apoplast) transport plays here a more general role than expected. This route is regulated by autophagy proteins, including recently discovered involvement of the exocyst subcomplex. Traffic from ER into the vacuole bypassing Golgi apparatus (GA) acts not only in stress-related cytoplasm recycling or detoxification, but also in developmentally-regulated biopolymer and secondary metabolite import into the vacuole (or apoplast), exemplified by storage proteins and anthocyanins. We propose that this pathway is relevant also for some phytohormones' (e.g., auxin, abscisic acid (ABA) and salicylic acid (SA)) degradation. We hypothesize that SA is not only an autophagy inducer, but also a cargo for autophagy-related ER to vacuole membrane container delivery and catabolism. ER membrane localized enzymes will potentially enhance the area of biosynthetic reactive surfaces, and also, abundant ER localized membrane importers (e.g., ABC transporters) will internalize specific molecular species into the autophagosome biogenesis domain of ER. Such active ER domains may create tubular invaginations of tonoplast into the vacuoles as import intermediates. Packaging of cargos into the ER-derived autophagosome-like containers might be an important mechanism of vacuole and exosome biogenesis and cytoplasm protection against toxic metabolites. A new perspective on metabolic transformations intimately linked to membrane trafficking in plants is emerging.
Keywords: Anthocyanins; biologický transport; autofagie; Golgiho aparát; Biological Transport; Cytoplasm; Plant Cells; regulátory růstu rostlin; Vacuoles; Autophagy; endoplazmatické retikulum; rostlinné buňky; vakuoly; Endoplasmic Reticulum; anthokyaniny; Golgi Apparatus; cytoplazma; Plant Growth Regulators